Semiconductor structure with dielectric layer

By introducing multiple defect types into semiconductor structural elements and moving along the same average effective spacing at the applied voltage and temperature, the problem of difficulty in optimizing service life in the prior art is solved, and the problem of achieving the use of different applications is achieved stability and long lifespan.

CN114080697BActive Publication Date: 2025-02-21ROBERT BOSCH GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080049174.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-08
Filing Date
2020-06-23
Publication Date
2025-02-21
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively optimize the service life of semiconductor structural components with a variety of active defect types, especially in different applications.

Method used

By fabricating thin-layer structural elements on a silicon substrate, at least two different defect types are introduced using at least one dielectric layer and two electrodes, so that these defect types are effective along the same average at the applied operating voltage and temperature spacing motion, thereby optimizing service life.

Benefits of technology

The service life of semiconductor structural components is achieved in different applications, and the dielectric breakdown time is extended and the stability of components is improved by adjusting the defect mobility in the dielectric layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114080697B_ABST
    Figure CN114080697B_ABST
Patent Text Reader

Abstract

The invention relates to a semiconductor component (200), comprising at least one dielectric layer (230) and at least one first electrode (202) and a second electrode (201). In addition, at least two different defect types (212, 215, 217) are present in the dielectric layer (230). The at least two different defect types (212, 215, 217) move toward one of the two electrodes (202, 210) along a local defect state (235) having an average effective distance a0 (210) respectively, depending on an operating voltage applied between the first electrode (202) and the second electrode (201) and a current operating temperature. For the average effective distance a0 (210), it is applicable that the average effective distance is greater than 3.2 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a semiconductor structural element. Background Art

[0002] In "Improved reliability predictions in high permittivity dielectric oxide capacitors under high de electric fields with oxygen vacancy induced electromigration" by CA Randall, R. Maier, W. Qu, K. Kobayashi, K. Morita, Y. Mizuno, N. Inoue and T. Oguni in Journal of Applied Physics 113, 014101 (2013), the jump of defect types (e.g., oxygen defects) present in the dielectric layer is described as the cause of breakdown in the dielectric layer. Here, the central model parameters are explained physically, but are empirically obtained by fitting with the stop time (Ausfallzeit) under the assumption that there is only one active defect type. There is no description of how these parameters are more accurately associated with the material. Here, complex stop mechanisms are not fully or not mapped at all, in which there are multiple defect types in the semiconductor layer. The service life prediction described there is only applicable if, under the current load conditions with a certain temperature and a certain electrical field, one defect type predominates and only leads to failure due to the accumulation of this defect type in the boundary layer.

[0003] The object of the present invention is to optimize the service life of semiconductor components having more than one active defect type, independently of the application of the semiconductor component (operating voltage, operating temperature). Summary of the invention

[0004] In order to achieve this object, a semiconductor component according to the invention is proposed. The semiconductor component is manufactured on a silicon substrate by means of thin-film technology and can be used as a piezoelectric actuator, for example, in the case of a MEMS component (e.g., a micromirror). In this case, the semiconductor component has at least one dielectric layer. In addition, the semiconductor component has at least one first electrode and a second electrode, via which an operating voltage is applied to the dielectric layer. In addition, at least two different defect types exist in the dielectric layer. These defect types can be defects (e.g., oxygen defects or lead defects), lattice destruction due to occupied interstitial positions (e.g., due to hydrogen), Frenkel defects, but can also be substitutional defects (e.g., by intentionally or unintentionally introduced foreign atoms). These defect types differ from each other, for example, in terms of their charge quantity. The at least two different defect types are configured to move toward one of the two electrodes along a local defect state having the same average effective spacing a0, respectively, according to the operating voltage applied between the first electrode and the second electrode and the current operating temperature. This state of motion of the defect type is also called jumping. The average effective distance a0 of the local defect states is a significant, measurable and influencing material property which characterizes the quality of the semiconductor component in terms of service life at the end of the production process. The average effective distance a0 is related to the mobility of the defects in the dielectric layer.

[0005] Semiconductor components with a relatively large distance from the jump center have the consequence that different defect types can move more poorly in the dielectric layer and can therefore accumulate more slowly on the boundary layer and continuously lead to dielectric breakdown. In this case, an average effective distance of more than 3.2 nm has been shown to be a value that leads to an optimized service life of the semiconductor component despite a large number of current defect types in the dielectric layer, regardless of the future application of the semiconductor component and the operating conditions that exist as a result. In particular, with an average effective distance a0=3.2 nm, a downtime of approximately 12 hours is obtained at a maximum voltage of 10 V and a maximum operating temperature of 100° C. For continuous operation of the PZT actuator, this downtime is suitable for products for entertainment electronics (e.g. micromirrors).

[0006] The structural element according to the invention shows a leakage current density J during the load period until dielectric failure. TED The time curve of the leakage current density is given by the equation according to the thermionic emission diffusion theory of Crowell and Sze

[0007]

[0008] Here, q represents the unit charge, N Crepresents the effective state density in the conduction band, v R represents the effective recombination velocity, v D represents the effective diffusion velocity, φ B eff represents the effective Schottky barrier, k B represents the Boltzmann constant, T represents the ambient temperature, and U represents the potential difference across the dielectric layer. That is, U describes the operating voltage applied to the two electrodes of the semiconductor component.

[0009] Due to the change of the effective Schottky barrier φ B eff (t) results in a time curve of the leakage current density. This characterizes the influence of the two boundary layers on the leakage current density, which are located between the two electrodes and the dielectric layer. The effective Schottky barrier is referred to as φ(t) in the following and includes all parts of the semiconductor electrode material transformation, the changes caused by the applied operating voltage and the changes caused by the accumulation of defects. The logarithm of the leakage current density reduces equation (1) to a time constant K and a time-varying term. This time-varying term reflects the processes inside the material, which are caused by the movement of all movable defects contained in the material:

[0010]

[0011] The term "defect" also includes structural changes in the construction.

[0012] The displacement of defects leads to defect accumulation in the dielectric layer as it approaches the electrode, which results in a change in the effective barrier height φ. Solving equation 2.1 in terms of φ yields:

[0013] Φ(t)=[ln(K)-ln(J TED (t))]k B T (2.2)

[0014] The time curve of the effective barrier height due to the accumulation of defects is described as follows:

[0015] In this case, generally, the accumulation and the associated change in the effective Schottky barrier at the two boundary layers φ + (t) and φ - The indices + and - here respectively mark changes in the boundary layer, which characterize the transition of minority carriers or majority carriers into the dielectric layer. The boundary layer has an initial barrier height φ0 and undergoes a barrier height change Δφ i, which is caused by defect type i. Due to the necessary charge neutrality, there must always be defect pairs or defect clusters (Defektansammlungen). This means that when defects with a negative charge appear, there are also defects with a positive charge in the material. The corresponding effects of the defects are marked by the indices + and -. Individual defects move in opposite directions in the applied electric field of the operating voltage depending on their charge. Defects with a positive charge migrate to the electrode with a negative potential and accumulate in the dielectric layer near this electrode. Defects with a negative charge move to the electrode with a positive potential in order to accumulate again near this electrode.

[0016] The barrier height change Δφ caused by defect type i i is characterized by its maximum height δφ i and the representative time constant τ i , in which the barrier height changes most strongly in this representative time constant:

[0017]

[0018] item This is an approximation for the statistical accumulation of the given defect distribution in the material. In this case, the maximum positive and negative heights of the potential barrier change δφ i + and δφ i - and the associated time constant τ i + and τ i - have different sizes because they involve different defects and different boundary layers. This is obtained with the help of formula (3.2):

[0019]

[0020] And for the time variation of the potential barrier, we get:

[0021]

[0022] Time constant τ i + / - It is defined by the mobility of the defect in the dielectric layer and the distance to be covered in this layer. When displaced in the dielectric layer, defect type i must cover the distance d between the center of gravity of its distribution and the boundary layer. i . Together with the speed v i Together, this yields a characteristic time constant for the accumulation process of defect type i:

[0023]

[0024] The structural element according to the invention is distinguished by the displacement of defects by jumping in the applied electric field of the operating voltage. Defect type i is along a plane with an average effective spacing a i The local defect state moves. This leads to a jump velocity v i , the jumping speed is described by the known variable range hopping method:

[0025]

[0026] Here, C 0,i (a i ) represents the following function: This function represents the influence of the local defect distribution. Here, as is common in the case of variable range jumps, the jump test frequency ν i It refers to the frequency with which the defect encounters the existing potential barrier. In addition, the defect jump probability overlaps with the wave function of the dihydrogen local defect The defect is proportional to the distance a between the local defect states. i The jump probability increases with the operating temperature through the real activation energy E associated with the material and defects. A,o,i Here, the real activation energy E A,o,i The activation energy is independent of the operating voltage and operating temperature. The hyperbolic sine function describes the directional reduction of the energy barrier during the jump process, which contains the charge N associated with the defect i. q,i , average local defect center distance a i The product of the electric field E. The electric field E is generated by the applied operating voltage U and the thickness d of the dielectric layer. If the average local defect center spacing a i As a increases, the mobility of defect i generally decreases for the described defect jumping case. i Compared with the dielectric layer, it has a large i The dielectric layer of is distinguished by the fact that in it, under the same operating conditions, ie the same operating voltage U and the same operating temperature T, defects move more slowly. This leads to a larger time constant τ for the accumulation of defects on the boundary layer between the dielectric layer and the electrode. i , and leads to a slower barrier height change Δφ i .

[0027] The structural element according to the invention is characterized in that the n defect types contained in the dielectric layer move on local defect states with the same average spacing a0, and therefore it applies that:

[0028] a1=a2...an =a0 (8)

[0029] The spacing of local defect states can be determined from leakage current measurement data J with knowledge of the physical modeling described previously. TED Extracted from. For dielectric failure under temperature load and voltage load, the average effective spacing is the core material property. This material property is independent of the operating voltage and operating temperature and can be influenced by the manufacturing process. This influence can be achieved, for example, by the choice of starting material when depositing the dielectric layer (for example, the choice of sputtering target) and / or by changes in process conditions during material deposition (for example, gas, power, temperature) and / or also by subsequent processes (for example, heat treatment, action of gas). For example, an increase in temperature during the deposition of the dielectric layer or a reduction in the growth rate caused by a lower plasma power leads to a higher crystalline quality. In addition, a reduction in the density of defect centers occurs here, which in turn leads to an increase in a0. In addition, the crystal structure can be changed by changing the target composition as a process condition. The target composition changes from Pb 1.3 (Zr 0.52 Ti 0.48 )O3Ni 0.005 To Pb 1.3 (Zr 0.52 Ti 0.48 )O3, for example after the growth of the dielectric layer, leads to an increase in a0 in the original material. A reduction in the hydrogen content as a process condition in a subsequent process (for example the deposition of a passivation in a hydrogen-containing plasma process) also leads to an increase in a0. In such a process, the hydrogen content can be reduced, for example, by using precursors with a lower hydrogen content, that is, for example, by using N2 instead of NH3 as a nitrogen source in the deposition of PECVD-SiN passivation. Another possibility to reduce hydrogen in the deposition of PECVD passivation to increase a0 is to reduce the hydrogen-containing gas flow or to use a low-hydrogen precursor. In addition to this, the dielectric layer can be protected from the influence of hydrogen-containing subsequent processes by using barriers (for example sputtered metal oxides: RuO, TiO, AlOx, etc.) in order to increase a0.

[0030] Furthermore, in principle, by reducing the temperature load as a process condition, for example by shortening the temperature load in time and / or lowering the temperature used, the outgassing of hydrogen from surrounding layers into the dielectric layer can be reduced in subsequent processes and a0 can thus be increased.

[0031] In the case of the structural element according to the invention, there is a critical barrier height φ for both boundary layers krit + / - If the critical barrier height changes by Δφ krit + / -A critical barrier height change in the local area at the time point t krit When one of the barrier heights is reached and exceeded, dielectric breakdown occurs locally. This means that when φ is reached krit + When , breakdown occurs via tunneling minority carriers (case 1):

[0032] φ krit + =φ0 + +∑ i Δφ i + (t krit )=φ0 + +Δφ krit + Among them, Δφ krit + =∑ i Δφ i + (t krit )(9.1)

[0033] On the contrary, when reaching φ krit - When , breakdown occurs via tunneling majority carriers (case 2):

[0034] φ krit - =φ0 - +∑ i Δφ i - (t krit )=φ0 - +Δφ krit - Among them, Δφ krit - =∑ i Δφ i - (t krit )(9.2)

[0035] At local krit When the leakage current density J increases locally, the semiconductor structure element is damaged locally. TED In the curve of krit , can either be a short rise followed by an immediate return (in < 1 s) for J between rises TED This is detected by a jump in the first case, or by a permanent jump. In the first case, the conduction path itself is thermally damaged. In the second case, the supplied electrical power is not sufficient to completely damage the conduction path. kritAfterwards, a semiconductor component remains which is locally damaged in a limited area. krit As the load increases, more and more local dielectric breakdowns occur, which ultimately lead to complete destruction of the semiconductor component. The first local breakdown is therefore an important and relevant measure for the service life of the semiconductor component.

[0036] Thus, by means of the physical description of the barrier height change (5) for the jump transport of n defect types (6) and (7), it is possible to determine the average effective spacing a0 of the local defect states from the curve of the leakage current density (1). By measuring a0 before and after the change during the production process, the semiconductor component according to the invention can be improved in a targeted manner. For this purpose, firstly, the semiconductor component is recorded at at least two operating voltages U1 and U2 and at a constant temperature until the time t krit The leakage current curve J until the dielectric breakdown TED Then, the equations (2.2) and (5) described above are treated equivalently, and the numerical fit is followed by J TED The time curve of τ results in the variable τ as a function of the operating voltage i According to the formulas (6), (7) and (8) described above, for a constant temperature T = T0, we get τ i The function related to the electric field E is:

[0037]

[0038] The representative time constant τ determined from the leakage current measurement at a constant temperature T=T0 and a varying voltage U1=E1 / d, U2=E2 / d i , in the case of n>1 defects, the parameter N can be determined from equation (10.1) by mathematical fitting q,i and a0. Here, according to the q,i The physical expectation value of is an integer multiple of the elementary charge e. The measured J TED The curves are subject to manufacturing fluctuations and tolerances caused by the measurement technique used. Therefore, the material properties a0, C 0,i (a0), N q,i and A,0,i The accuracy of can be improved by increasing the number of samples and also by additional measurement data in the case of more than two voltages.

[0039] After changing the process conditions, the determination of a0 is repeated in order to show the physical impact of the process changes on the material property a0 which has a central influence on the defect mobility.

[0040] When ln(τ i (E; T0)) when plotted over voltage, yields an intuitive graphical representation. Here, (10.1) becomes:

[0041]

[0042] With the help of And for large independent variables x, we can use Equation (10.2) for large electric fields E can be further simplified to:

[0043]

[0044] Therefore, in the case of ln(τ i A graphical representation of (E; T0 / sek)) as a function of the operating voltage for i defect types is obtained with a slope m i In the case of a constant temperature T0, except for the known constant k B In addition to T0, through the defect charge N q,i and the average effective spacing a0 of the local defect centers define the slope m i For small E, (10.2) still applies, but the graph then deviates significantly from the straight line. In equation (10.3), the straight line clearly passes through K along the Y axis. i (a0) shift. K i (a0) refers to the voltage- and temperature-independent local effect of the average effective spacing a0 of local defect centers on the jumping velocity described in (7.1).

[0045] Preferably, the average effective spacing a0 of the dielectric layers of the semiconductor component has a value greater than 3.24 nm. Such a material has a lower defect mobility than a material having an average effective spacing of 3.2 nm. This in turn leads to an increased service life of the semiconductor component.

[0046] In practice, dielectric layers are more often found in which more than just two defect types are present. In the exemplary case of a PZT layer, there is at least a local excess or deficiency of atoms Pb, Ti and Zr. In addition, in practice there are operating conditions (that is to say combinations of operating temperature T and operating voltage U) in which more than two defects make a significant and relevant contribution to the electrical failure of the dielectric layer. In the semiconductor components described here, a correspondingly higher number of dielectric layers can be used and operation can be performed over a wider range of operating conditions.

[0047] The dielectric layer is preferably designed as a polycrystalline high-k oxide dielectric and in particular as a PZT layer (PZT=Pb[Zrx Ti 1-x ]O3), doped PZT layer (Pb[Zr x Ti 1-x-y ]O3Ni y ), KNN layer (KNN = [K x Na 1-x ]NbO3), HfO2, ZrO2 or SrTiO3. Preferably, the sputtered PZT layer of the semiconductor component has Pb 1.3 (Zr 0.52 Ti 0.48 )O3 or Pb 1.3 (Zr 0.52 Ti 0.48 )O3Ni 0.005 In addition, preferably, additional defects can be introduced into the high-k dielectric by doping in order to influence the barrier height variation ΔΦ.

[0048] Preferably, the dielectric layer is designed as a sputtered PZT layer. In this case, the so-called target material is deposited on the substrate in a plasma. For example, PZT is used as the target material. Preferably, in this context, the sputtered PZT layer has a deposition temperature of less than 500° C. In the case of such a dielectric layer, the following effect can be demonstrated: the smaller the existing defect mobility in the sputtered PZT layer, the higher the service life of the semiconductor component. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1a The graphs of leakage current measurements are shown for three different dielectric layers.

[0050] Figure 1b The time curve of the effective barrier height resulting from leakage current measurements and the breakdown of the contribution to the present defect type are shown.

[0051] Figure 2a The graphs show the curves of four leakage current measurements determined at the same operating temperature but different operating voltages on the dielectric layer and the corresponding matched model curves.

[0052] Figure 2b The electric field-dependent curves show the time constants of the defect types involved.

[0053] Figure 3 The electric field-dependent curves of the time constants of the defect types involved are shown for three different dielectric layers.

[0054] Figures 4a to 4d The movement of different defect types in a dielectric layer along local defect states, each having an average effective spacing a0, is schematically shown.

[0055] Figure 5 The downtime t is shown as a function of the average effective spacing a0 of the local defect centers for four dielectric layers and two operating conditions. krit changes.

[0056] Figure 6a The results show that the Pb as dielectric layer is different under the same operating temperature but different operating voltages. 1.3 (Zr 0.52 Ti 0.48 )O3Ni 0.005 The curves of the three leakage current measurements obtained above and the corresponding matched model curves.

[0057] Figure 6b The electric field-dependent curves show the time constants of the defect types involved. DETAILED DESCRIPTION

[0058] Figure 1a A curve 14 is shown for leakage current measurement of a dielectric layer of a semiconductor structure element, which is referred to as Example 1 below. In this case, the time is plotted logarithmically in seconds on the X-axis 12 and the leakage current density is plotted logarithmically in amperes per square centimeter on the Y-axis 10. Example 1, which is provided for leakage current measurement, has a silicon substrate having a dielectric passivation layer and a first electrode deposited on the passivation layer. The first electrode has a double layer made of 110 nm thick PVD platinum, which is covered by a 110 nm conductive lanthanum nickel oxide buffer layer (referred to as LNO layer below). The LNO layer is also applied by PVD. The dielectric layer located on the first electrode has a thickness of 1 μm and is deposited in an RF-PVD process at a temperature of 480° C. and Pb 1.3 (Zr 0.52 Ti 0.48 )O3. The remaining process parameters of the deposition described above are selected such that the dielectric layer grows polycrystalline and preferably with a (100) c-axis orientation. The second electrode of the semiconductor element is applied to the dielectric layer by PVD, which second electrode is a 110 nm thick platinum electrode. The semiconductor component according to Example 1 is passivated and does not undergo thermal post-treatment after the electrical contacting.

[0059] also, Figure 1a A curve 16 shows a leakage current measurement of a dielectric layer of a further semiconductor component, which is referred to below as Example 2.

[0060] The production of Example 2 was carried out in a similar manner to Example 1, however, the structural element was subjected to a thermal post-treatment after the electrical contacting. The thermal post-treatment was carried out at 450° C. in a nitrogen atmosphere at 60 mbar for 40 minutes.

[0061] also, Figure 1a The curve 18 shows the leakage current measurement of the dielectric layer of a further semiconductor component, which is referred to below as Example 3. The production of Example 3 was carried out similarly to Example 1, but the component was subjected to a thermal post-treatment after the electrical contacting. The thermal post-treatment was carried out at 500° C. in a nitrogen atmosphere of 60 mbar for 40 minutes.

[0062] Before the leakage current curves were measured, all described exemplary embodiments 1, 2 and 3 were covered with a passivation layer and were electrically contacted with an aluminum conductor path.

[0063] All three exemplary embodiments were measured up to the respective dielectric breakdown 15, 17 and 19. As can be seen here, depending on the production of the dielectric layer, very different leakage current curves 14, 16 and 18 with different breakdown times 15, 17 and 19 result.

[0064] Figure 1b Example 2 shows the Figure 1a The model parameters are extracted from the leakage current curve 16 measured on the X axis 32. Here, the time is again plotted logarithmically in seconds on the X axis 32, and the barrier height change Δφ is plotted logarithmically in electron volts on the Y axis 30. The curve 38 shows the time-dependent curve Δφ(t) of the barrier height change starting from the initial barrier height φ0 34.

[0065] This curve Δφ(t) 38 of the barrier height variation is obtained by the following formula (see formula 2.2 above):

[0066] Φ(t)=[ln(K)-ln(J TED (t))]k B T

[0067] The determined time profile of the mean effective barrier height φ(t) is then numerically adapted to the formula (see above formula 3.2):

[0068]

[0069] Different Δφ are obtained from this numerical fit i + / - (t), Δv i + / - (t) describes the curve of Δφ(t). Thus, in the case shown, by Δva - (t)39 curve, Δφ b - (t)40 curve and Δφ c - The curve of (t)42 together with the curve Σ i Δφ i + 36 and Δφ(t)38. According to the following formula (see above

[0070] Formula 5.1)

[0071]

[0072] Then we can find different τ i + / - In this case, the barrier height change Δφ for the majority carriers i - 39, 40 and 42, obtain the corresponding representative time constant τ a , τ b and τ c The characteristic time constants of these are Figure 1b 47a, 47b and 47c are respectively marked in FIG. 4 and are the time points at which the corresponding barrier height change changes most strongly. In order to improve the overview, the barrier height change Δφ for minority carriers is not explicitly shown separately. i + The curve Σ only shows the variation of the barrier height. i Δφ i + 36, the sum curve has a single time constant τ d , τ e and τ f 49a, 49b and 49c. In this case, respective characteristic time constants are assigned to the defect types a, b, c, d, e and f present in the layer, and accordingly six mutually different defect types are present in the dielectric layer.

[0073] exist Figure 1b In the case shown above, the dielectric breakdown 47 of the dielectric layer occurs by tunneling majority carriers according to the following formula (see Formula 9.2 above):

[0074] φ krit - =φ0 - +∑ i Δφ i - (t krit )=φ0 - +Δφkrit - , where φ krit - =∑ i Δφ i - (t krit )

[0075] That is, Δφ a - (t)39, Δφ b - (t)40 and Δφ c - (t)42 is the sum of the previously determined curves and the resulting barrier height change Σ according to its curve i Δφ i - 44. If at time t krit When a barrier height change 46 of the dielectric layer that is critical for majority charge carriers is reached 48 , a local breakdown of the layer occurs due to the different existing defect types a, b and c, which have accumulated in the boundary layer between the dielectric layer and the electrode.

[0076] Figure 2a The leakage current curves measured in Example 2 are shown for different operating voltages and a constant operating temperature of 100° C. Here, too, the time is plotted logarithmically in seconds on the X-axis 62 and the leakage current density is plotted logarithmically in amperes on the Y-axis 60. The leakage current curve 100 was measured at an operating voltage of 5 volts, the curve 92 was measured at an operating voltage of 10 volts, the curve 76 was measured at an operating voltage of 15 volts, and the curve 68 was measured at an operating voltage of 20 volts. The measurements were carried out until the respective dielectric breakdown 66, 82, 94 and 102 of the dielectric layer. By comparing the measured current curves 76, 92 and 100 with the associated model curves 78, 90 and 104, it can be seen that the applied thermionic emission diffusion theory and the effective barrier height that can change in time due to movable defects are in good agreement with the measured curves.

[0077] The points 106a, 106b and 106c marked in the leakage current curve 100 represent the Figure 1a and Figure 1b The characteristic time constant τ for this curve determined by the described method is a , τ b and τ c Correspondingly, the points 98a, 98b and 98c marked in the leakage current curve 92 represent the determined characteristic time constant τ for this curve. a , τb and τ c Furthermore, the points 80a and 80b marked in the leakage current curve 76 represent the determined characteristic time constant τ for this curve. a and τ b The points 72 a and 72 b marked in the leakage current curve 68 represent the determined characteristic time constant τ for this curve. a and τ b Each representative time constant τ a , τ b and τ c In the present measurement, one defect type a, b and c is respectively assigned to the defect present in the dielectric layer.

[0078] Figure 2b The time constant τ showing the current defect type i Here, the electric field is plotted in volts per meter on the X-axis 112 and the representative time constant τ is plotted in a unitless manner on the Y-axis 110. i The natural logarithm of . Here, the X-axis segment 140 marks the electric field applied to the dielectric layer at an operating voltage of 5 volts. Accordingly, the vertical line through the axis segment 140 is found again from the leakage current curve 100 Figure 2a The characteristic time constants 106a, 106b and 106c identified in the leakage current curve have corresponding scattering widths of the measurement data 107a, 107b and 107c. The X-axis segment 142 marks the electric field applied to the dielectric layer at an operating voltage of 10 volts. Accordingly, the vertical line through the axis segment 142 is found again from the leakage current curve 92. Figure 2a The characteristic time constants 98a, 98b and 98c identified in the leakage current curve have the corresponding scattering widths of the measurement data 99a, 99b and 99c. The X-axis segment 144 marks the electric field applied to the dielectric layer at an operating voltage of 15 volts. Accordingly, the vertical line through the axis segment 144 is used to find the leakage current curve 76 from Figure 2a The characteristic time constants 80a and 80b identified in the leakage current curve have a corresponding scattering width of the measurement data 81a. The X-axis segment 146 marks the electric field applied to the dielectric layer at an operating voltage of 20 volts. Accordingly, the vertical line through the axis segment 146 is again found from the leakage current curve 68 Figure 2a With the characteristic time constants 72a and 72b identified in FIG. 7 , the leakage current curve has a corresponding scattering width of the measurement data 73a.

[0079] According to the formula (10.3) derived above

[0080]

[0081] For defect types a, b and c, the slope m a 、m b and m c The straight lines 114, 116 and 118, for a constant a0, this produces an integer defect charge N q,a 、N q,b and N q,c The straight lines 114, 116 and 118 pass through a constant K which depends on a0. a , K b and K c Shift along the Y axis.

[0082] Figure 3 The logarithmic, electric field-dependent curves of the time constants of the present defect types are shown for three dielectric layers at 100° C. The electric field is plotted in volts per meter on the X-axis 112 and the representative time constant τ is plotted in unitless form on the Y-axis 170 i The natural logarithm of . The X-axis segment 142 marks the electric field applied to the dielectric layer when the operating voltage is 10 volts. Figure 2b , the identified representative time constant τ is found again in the vertical line passing through the axis segment 142 a 98a and τ b 98b, which has the associated scattering width for the measurement data 99a and 99b of Example 2. Likewise, the identified representative time constant τ is found again in the perpendicular line relative to the axis segment 142. a 128a and τ b 134a, which has the associated scatter width for the measurement data 135a of Example 3. Furthermore, the identified representative time constant τ is found again in a perpendicular line relative to the axis segment 142 a 130b and τ b 136b, the representative time constant has the associated scattering width for the measurement data 161b and 137b of Example 1. The X-axis segment 144 marks the electric field applied to the dielectric layer at an operating voltage of 15 volts. Figure 2b , the identified characteristic time constant τ is found again in the vertical line through the axis segment 144 a 80a and τ b 80b, which has the associated scattering width for the measurement data 81a of Example 2. Likewise, the identified representative time constant τ is found again in the perpendicular line relative to the axis segment 144. a129a and τ b 135a, which has the associated scattering width for the measurement data 151a and 152a of Example 3. Furthermore, the identified representative time constant τ is found again in a perpendicular line relative to the axis segment 144 a 131b and τ b 137b, the representative time constant has the associated scattering width for the measurement data 162b and 153b of Example 1. For defect type a, a straight line 120 is obtained for Example 3, a straight line 114 is obtained for Example 2, and a straight line 122 is obtained for Example 1. Each of the straight lines 114, 120 and 122 has a different slope m a and the displacement K along the Y axis a (a0), the displacement is caused by the corresponding different average effective spacing a0. For defect type b, a straight line 124 is obtained for Example 3, a straight line 116 is obtained for Example 2, and a straight line 126 is obtained for Example 1. Each of the straight lines 116, 124 and 126 also has a different slope m b and the displacement K along the Y axis b (a0), the displacement is caused by a correspondingly different average effective distance a0.

[0083] Figure 4a The semiconductor structure element 200 at a first time point t0 is schematically shown. The semiconductor structure element 200 comprises a dielectric layer 230 with a layer thickness 208. For example, the dielectric layer 230 can be a PZT layer. In addition, the semiconductor structure element 200 has a first electrode 202 and a second electrode 201, which are arranged opposite to each other. In addition, a boundary layer 203 or 204 is arranged between the corresponding electrode 201 or 202 and the dielectric layer 230. There are different defect types in the dielectric layer 230, which are exemplarily marked as defect type 212 with a single positive charge 214 and defect types 215 and 217 with a single negative charge 216. The indexes + and - mark the number of charge carriers of the corresponding defect type. Due to the necessary charge neutrality in the dielectric layer 230, there are defect pairs or defect clusters. That is to say, when defects with negative charges 215 and 217 appear, defects with positive charges 212 are also present in the material. Different defect types 212, 215 and 217 are arranged in local impurities 235 on. Figure 4a At the first time t0 shown above, no voltage and therefore no electric field is applied between the electrodes 201 and 202 .

[0084] Figure 4bThe semiconductor structure element 200 is shown at a second time point t1 after the first time point t0. At this time point t1, a voltage is applied between the first electrode 202 and the second electrode 201, and an electric field 220 is thus generated in the dielectric layer 230. Now, depending on the operating voltage applied between the first electrode 201 and the second electrode 202 and the current operating temperature, different defect types 212, 215 and 217 move along local defect states 235. This state of motion of defect types 212, 215 and 217 is also called jumping. The local defect states 235 each have the same average effective spacing a0 210. In this case, the average effective spacing a0 210 is greater than 3.2 nm. The defect type 212 with a positive charge 214 migrates to the electrode with a negative potential (in this case, the first electrode 202) and accumulates in the boundary layer 203 there. In contrast, defect types 215 and 217 having a negative charge 216 move to the electrode having a positive potential (in this case, the second electrode 201 ) in order to accumulate in the boundary layer 204 there. TED The carriers that want to reach from one electrode to the other must overcome the Schottky barriers φ(t) which are affected by the boundary layers 203 and 204. These barriers have an initial barrier height φ0 and undergo a barrier height change Δφ due to the defect types that accumulate there. i .

[0085] Figure 4c The semiconductor component 200 is shown at a third time t2 after the second time t1. In this case, a plurality of different defect types 212, 215 and 217 have accumulated on the boundary layers 202 and 203 of the dielectric layer 230 and have caused a barrier height change Δφ there. i At a fourth time t3 after the third time t2, a critical barrier height φ is reached at one of the boundary layers 202 or 203. krit As in Figure 4d As can be seen in FIG. 2 , a local dielectric breakdown 225 of the dielectric layer 230 now occurs. krit Afterwards, a semiconductor component 200 remains which is locally damaged on a limited surface. krit As the load increases, more and more local dielectric breakdowns 225 occur, which eventually lead to complete destruction of the semiconductor structure 200.

[0086] Figure 5 The downtime t is shown as a function of the average effective spacing a0 of the local defect centers for three dielectric layers and three operating conditions. kritThe downtime is plotted exponentially in hours (h) on the Y-axis 300 and the average effective spacing a0 is plotted linearly in nanometers (nm) on the X-axis. Reference 335 marks the determined downtime t of Example 3 when a0 is currently 3.24 nm, the operating voltage is -20 volts and the operating temperature is 150° C. krit =46 s. Reference numeral 336 indicates the determined idle time t of Example 2 when a0 is currently 3.49 nm, the operating voltage is −20 V, and the operating temperature is 150° C. krit =192 s. Reference numeral 337 indicates the determined idle time t of Example 1 when a0 is 3.65 nm, the operating voltage is −20 V, and the operating temperature is 150° C. krit =305s.

[0087] By connecting the reference characters 335 , 336 and 337 , a straight line 340 is obtained, which shows how the average effective distance a0 can be changed by correspondingly different heat treatments of the exemplary embodiments and how a greater average effective distance a0 also leads to a greater downtime t krit .

[0088] Reference numeral 345 indicates the determined idle time t of Example 3 at the present a0 of 3.24 nm, an operating voltage of −2.5 V, and an operating temperature of 175° C. krit =2.95*10 4 Reference numeral 346 indicates the determined idle time t of Example 2 when a0 is currently 3.49 nm, the operating voltage is −2.5 V, and the operating temperature is 175° C. krit =1.11*10 5 Reference numeral 347 indicates the determined idle time t of Example 1 when a0 is 3.65 nm, the operating voltage is −2.5 V, and the operating temperature is 175° C. krit =3.99*10 5 s.

[0089] Due to different operating conditions compared to 335, 336 and 337, the markers 345, 346 and 347 have much higher downtimes. However, here too, by connecting the markers 345, 346 and 347, a straight line 350 is obtained, which confirms the previously described relationship and thus shows the average effective distance a0 as a function of the downtime t krit The relationship between applies regardless of the current operating conditions.

[0090] Reference numeral 365 indicates the determined idle time t of Example 3 when a0 is currently 3.24 nm, the operating voltage is −10 V, and the operating temperature is 100° C.krit =5.25*10 4 Reference numeral 366 indicates the determined idle time t of Example 2 when a0 is currently 3.49 nm, the operating voltage is −10 V, and the operating temperature is 100° C. krit =1.1*10 5 Reference numeral 367 indicates the determined idle time t of Example 1 when a0 is currently 3.65 nm, the operating voltage is -10 V, and the operating temperature is 100° C. krit =2.42*10 5 s.

[0091] After the symbols 365 , 366 and 367 are connected, a straight line 370 is obtained which confirms the previously described relationship and thus shows the average effective distance a0 as a function of the idle time t krit The relationship between them applies regardless of the current operating conditions. In the case of a0 = 3.2 nm, a downtime of 12 hours is obtained with respect to the straight line 370. For the design of PZT actuators, continuous operation for more than 12 hours at a maximum voltage of 10 V and a maximum operating temperature of 100° C. is a realistic requirement for entertainment electronics products (e.g., micromirrors).

[0092] For the tested examples 1, 2 and 3, three different defect types a, b and c can be identified, respectively, which contribute to Σ i Δφ i - Responsible. On the one hand, there is defect type a with a current charge of 1e and a current true activation energy of 0.92eV. In the current embodiment, this defect type can associate with hydrogen or OH groups in the dielectric layer. On the other hand, there is defect type b with a current charge of 3e and a current true activation energy of 0.95eV. In the current embodiment, this defect type can associate with lead and / or titanium in the dielectric layer. Defect type c has a current charge of 4e and a true activation energy of 0.855eV. In the current embodiment, this defect type can associate with lead, titanium and / or zirconium in the dielectric layer.

[0093] Furthermore, for the tested embodiments 1, 2 and 3, three different defect types d, e and f can be identified, respectively, which contribute to Σ i Δφ i +On the one hand, there is defect type d with a charge of 1e and a current true activation energy of less than 0.8eV. In the current embodiment, this defect type can associate with hydrogen in the dielectric layer. On the other hand, there is defect type e with a current charge of 2e and a current true activation energy of 1.04eV. In the current embodiment, this defect type can associate with oxygen or lead in the dielectric layer. Defect type e has a current charge of 2e and a true activation energy of 1.22eV. In the current embodiment, this defect type can associate with lead in the dielectric layer.

[0094] Figure 6a Pb as a dielectric layer of a semiconductor structure element is shown 1.3 (Zr 0.52 Ti 0.48 )O3Ni 0.005 The leakage current measurement curves 404, 406 and 408 of the semiconductor structure element are referred to as Example 4 below. The production of Example 4 is carried out similarly to Example 1, but a target composition of Pb has been deposited. 1.3 (Zr 0.52 Ti 0.48 )O3Ni 0.005 dielectric layer.

[0095] The leakage current was measured at different operating voltages and a constant operating temperature of 150°C. Figure 6a . Here, the time is plotted logarithmically in seconds on the X-axis 402 and the leakage current is plotted logarithmically in amperes on the Y-axis 400. The leakage current curve 408 was measured at an operating voltage of 5 volts, the curve 406 was measured at an operating voltage of 10 volts, and the curve 404 was measured at an operating voltage of 15 volts. The measurements were performed until the corresponding dielectric breakdown 410, 412 and 414 of the dielectric layer. By comparing the measured current curves 404, 406 and 408 with the associated model curves 422, 430 and 438, it can be seen that the applied thermal ion emission diffusion theory and the effective barrier height that can be changed in time due to movable defects are in good agreement with the measured curves.

[0096] The points 432, 434 and 436 marked in the leakage current curve 408 represent the Figure 1a and Figure 1b The characteristic time constant τ for this curve, determined analogously to the method described above for Examples 1 to 3 g , τ h and τ j Correspondingly, the points 424 , 426 and 428 marked in the leakage current curve 406 represent the determined characteristic time constant τ for this curve. g , τh and τ j In addition, the points 416 , 418 and 420 marked in the leakage current curve 404 represent the determined characteristic time constant τ for the curve. g , τ h and τ j Each representative time constant τ g , τ h and τ j In the present measurement, one of the defect types g, h and j present in the dielectric layer is respectively assigned to it.

[0097] Figure 6b A graph showing the logarithm of the time constant of the current defect type divided by seconds as a function of the electric field is shown. Here, the electric field is plotted in volts per meter on the X-axis 451 and the representative time constant τ is plotted in a unitless manner on the Y-axis 450 i Here, the x-axis segment 455 marks the electric field applied to the dielectric layer at an operating voltage of 5 volts. Accordingly, the vertical line through the axis segment 455 is used to find the leakage current curve 408 from Figure 6a The characteristic time constants 432, 434 and 436 identified in the leakage current curve have the corresponding scattering widths of the measurement data 481, 484 and 508. The X-axis segment 460 marks the electric field applied to the dielectric layer at an operating voltage of 10 volts. Accordingly, the vertical line through the axis segment 460 is found again from the leakage current curve 406. Figure 6a The characteristic time constants 424, 426 and 428 identified in the leakage current curve have corresponding scattering widths of the measurement data 488, 498 and 512. The X-axis segment 465 marks the electric field applied to the dielectric layer at an operating voltage of 15 volts. Accordingly, the vertical line through the axis segment 465 is found again from the leakage current curve 404. Figure 6a With the characteristic time constants 416 , 418 and 420 identified in FIG. 4 , the leakage current curve has corresponding scattering widths of the measurement data 492 , 482 and 516 .

[0098] According to formula (10.3), for defect types g, h and j, the slope m is obtained. g 、m h and m j The straight lines 480, 494 and 504, for a constant a0 = 3.1 nm, this produces an integer defect charge N q,g =2, N q,h =3 and N q,j = 4. Lines 480, 494 and 504 pass through a constant K that depends on a0. g , K hand K j Shift along the Y axis.

Claims

1. A semiconductor structure element (200), comprising: at least one dielectric layer (230), and at least one first electrode (202) and a second electrode (201), In which, at least two different defect types (212, 215, 217) are present in the dielectric layer (230), wherein at least two different defect types (212, 215, 217) move toward one of the two electrodes (201, 202) along a local defect state (235) having an average effective spacing a0 (210) respectively according to an operating voltage applied between the first electrode (202) and the second electrode (201) and a current operating temperature, wherein a0 (210)>3.2 nm applies.

2. The semiconductor structure (200) according to claim 1, characterized in that It applies that a0(210)>3.24nm.

3. The semiconductor structure (200) according to claim 1 or 2, characterized in that At least three mutually different defect types (212, 215, 217) exist in the dielectric layer (230).

4. The semiconductor structure (200) according to claim 1 or 2, characterized in that The dielectric layer (230) is constructed as a polycrystalline oxide high-k dielectric.

5. The semiconductor structure (200) according to claim 4, characterized in that The dielectric layer (230) is configured as a sputtered PZT layer.

6. The semiconductor structure (200) according to claim 5, characterized in that The sputtered PZT layer has a deposition temperature of less than 500°C.

7. The semiconductor structure (200) according to claim 5, characterized in that The sputtered PZT layer has Pb 1.3 (Zr 0.52 Ti 0.48 )The composition of O3.

8. The semiconductor structure (200) according to claim 4, characterized in that The dielectric layer (230) is configured as a PZT layer or a KNN layer.

Citation Information

Patent Citations

  • SiC schottky barrier semiconductor device

    CN101221989A

  • Electronic structural elements with self-insulating cells

    CN106531695A